Polymorph selection towards photocatalytic gaseous CO2 hydrogenation - Tingjiang Yan (Nature Portfolio, 2019)
Polymorphs, compounds with identical chemical stoichiometries yet different atomic configurations, expand the range of potential chemical properties and new applications. Here, authors show rhombohedral indium oxides to be highly active and selective for photocatalytic CO2 hydrogenation.